2020
DOI: 10.3390/jcm9040951
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Metabolomics Biomarkers for Identifying High Risk Patients with Extranodal Extension in Oral Squamous Cell Carcinoma

Abstract: Extranodal extension (ENE) is an independent adverse prognostic factor in oral squamous cell carcinoma (OSCC), and is difficult to identify preoperatively. We aimed to discover biomarkers for high risk patients with ENE. Tandem tissue, plasma, and urine samples of 110 patients with OSCC were investigated through 600-MHz nuclear magnetic resonance (NMR) metabolomics analysis. We found that the levels of creatine, creatine phosphate, glycine, and tyramine in plasma significantly decreased in stage IV ENE positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Amino acid catabolism is a crucial component for cancer cell proliferation and progression, as it is involved in various processes such as nucleotide synthesis, lipogenesis, metastasis, epigenetic modifications, and evasion of tumor recognition by the immune system [ 25 ]. Phenylalanine is one of the essential amino acids, and the importance of phenylalanine metabolism has been identified in several human cancers, including colorectal cancer [ 26 ] and oral squamous cell [ 27 ] and non-small cell lung carcinoma, whereas phenylalanine restriction was associated with decreased tumor invasion in melanoma [ 28 ]. This study identified N-Acetylphenylalanine, an N-acetylated form of phenylalanine (Pubchem, [ 12 ]), to be significantly upregulated in the UC group, indicating a probable role of this metabolite in canine UC.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid catabolism is a crucial component for cancer cell proliferation and progression, as it is involved in various processes such as nucleotide synthesis, lipogenesis, metastasis, epigenetic modifications, and evasion of tumor recognition by the immune system [ 25 ]. Phenylalanine is one of the essential amino acids, and the importance of phenylalanine metabolism has been identified in several human cancers, including colorectal cancer [ 26 ] and oral squamous cell [ 27 ] and non-small cell lung carcinoma, whereas phenylalanine restriction was associated with decreased tumor invasion in melanoma [ 28 ]. This study identified N-Acetylphenylalanine, an N-acetylated form of phenylalanine (Pubchem, [ 12 ]), to be significantly upregulated in the UC group, indicating a probable role of this metabolite in canine UC.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB-dependent cytokines, matrix metalloproteinases (MMPs) and pro-inflammatory cytokines in saliva may be involved in the relationship between oral malignancies and aging, involving the senescence-associated secretory phenotype (SASP), and inflammatory diseases, such as oral mucosal ulcers and periodontitis [ 42 ]. Metabolome biomarkers in OSCC were also investigated using nuclear magnetic resonance (NMR) metabolomics to detect high-risk patients with an extranodal extension [ 43 ]. Recent research has revealed that EVs, including exosomes (small vesicles) and bigger vesicles, are released into the saliva from oral cancer lesions and/or oral tissues [ 44 ].…”
Section: Liquid Biopsy and Cancer Managementmentioning
confidence: 99%
“…Metabolome biomarkers in OSCC were also examined to identify high-risk patients with extranodal extension by using Nuclear Magnetic Resonance (NMR) metabolomics [ 16 ].…”
Section: Liquid Biopsymentioning
confidence: 99%